Acetylation-enhanced Sp1 transcriptional activity suppresses Mlph expression - Chan Song Jo; Hairu Zhao; Jae Sung Hwang (Scientific Reports)
Abstract Melanosome transport is regulated by major proteins, including Rab27a, Melanophilin (Mlph), and Myosin Va (Myo-Va), that form a tripartite complex. Mutation of these proteins causes melanosome aggregation around the nucleus. Among these proteins, Mlph is a linker between Rab27a and Myo-Va. There are some studies about the regulation of Mlph transcriptional expression. However, its regulation by post-translational modifications remains unclear. In this study, inhibition of HDACs by SAHA and TSA disrupted melanosome transport, causing melanosome aggregation. Specifically, we identified a novel mechanism in which HDAC5 regulates Mlph expression via Sp1. Knockdown of HDAC5 increased the acetylation of Sp1 and the binding to the Mlph promoter, thereby modulating its expression. This study highlights the crucial role of HDAC5 in melanosome transport through its interaction with Sp1. These findings suggest that HDAC5-mediated deacetylation is pivotal in the post-translational modification of melanosome transport, providing insights into the molecular mechanisms underlying this process.